Enhanced and sustained biodistribution of HIV-1 neutralizing antibody VRC01LS in human genital and rectal mucosa - Lemos, Maria P.; Astronomo, Rena D.; Huang, Yunda; Narpala, Sandeep; Prabhakaran, Madhu; Mann, Philipp; Paez, Carmen A.; Lu, Yiwen; Mize, Gregory J.; Glantz, Hayley; Westerberg, Katharine; Colegrove, Hunter; et al. (Nature communications, 2024)
To prevent sexually-acquired HIV-1 infection by immunoprophylaxis, effective concentrations of broadly neutralizing antibodies are likely needed at mucosal sites of exposure. Here, we examine the biodistribution of monoclonal antibody VRC01 and its extended half-life variant, VRC01LS, in colorectal and genitourinary tracts of healthy adults 1-52 weeks after intravenous infusion. At 1-2 weeks, VRC01LS levels are ~3-4 times higher than VRC01 in serum ( p = 0.048), rectal ( p = 0.067), vaginal ( p = 0.003) and cervical tissues ( p = 0.003); these differences increase over time. Both antibodies primarily localize within rectal lamina propria and cervicovaginal stroma, with limited and variable epithelial distribution. Although 8-28% of serum mAb levels reach mucosal tissues, <3% are in seminal and rectal secretions. Elimination half-lives in mucosal tissues are 20-28 days for VRC01 and 51-68 days for VRC01LS. Thus, VRC01LS infusion achieves higher, sustained concentrations in human mucosal tissues than VRC01, supporting the future investigation of potent, long-acting LS-modified antibodies to prevent HIV-1. Antibody immunoprophylaxis for HIV-1 will require effective concentration of biologics at mucosal sites of exposure for effectivity. Here the authors show that infused Fc-modified VRC01LS antibody has increased levels in blood, in the female genital tract and male rectal tissue, compared to native antibody VRC01. VRC01LS is detectable for more than year at the sites of sexual HIV transmission.